Odmienne koncepcje homilii, ich egzemplifikacja i komparatywna analiza - Sławiński, Henryk (Studia Pastoralne, 2009)
Through comparison, this article presents two concepts of the homily, which have been discussed in the Church since the Second Vatican Council until the last interventions delivered by the members of the world Synod of Bishops on the „Word of God in the Life and Mission of the Church”, held in October 2008 at the Vatican. After a brief presentation of the contemporary discussions on the concept of the homily, two texts of homilies based on different concepts are presented and accompanied by a side by side in-depth analysis. The conclusion states that it’s not enough to teach someone in order to make of him, or her, a good Christian. To reach this aim – far more then teaching – it seems appropriate to facilitate an aware participation of the faithful in the celebrated mystery of Christ and to shine the light of that mystery on their daily life.